THE DETERMINNATION OF RESIDUAL STRESS OF GEAR TOOTH ROOT BASED ON X-RAY TECHNOLOGY - WANG Zhen; HU TianTong; FENG XianZhang; MENG XiangZhi (Jixie qiangdu, 2017)
Transverse residual stress of tooth root has significant influence on bending fatigue strength of gears.But given the geometry of gears,using the method of exposing teeth root to complete determination of transverse residual stress at present,it not only destroys the original stress state of material surface,but conflicts with the concept of residual stress measurement by Xray nondestructive.so in order to do not cut gears,which can also more accurately measure transverse residual stress of the gear tooth root,in this paper,through combining with the theoretical analysis and experimental verification method,the relationship of transverse and longitudinal residual stress of the gear tooth root is derived.With the known of Bragg Angle of free stress— θ0,the transverse residual stress of Gear tooth root can be calculated by the size of the longitudinal residual stress through the X-ray method measured,so it is convenient to measure the transverse residual stress of gear tooth root.